Development of peripheral chemoreceptor function in infants with chronic lung disease and initially lacking hyperoxic response. Issue 1 (July 1996) - Katz-Salamon, M; Eriksson, M; Jónsson, B
Abstract : Ten preterm infants with chronic lung disease (CLD) and undeveloped peripheral chemoreceptor function, described as ventilatory response to hyperoxia, were investigated, according to an individual protocol. Each infant was followed up until the response to hyperoxic inhalation had been observed on two occasions. Each examination consisted of overnight recording of saturation, testing of lung compliance and airway resistance, and the hyperoxic test. The hyperoxic response appeared at a mean postnatal age of 14 weeks (range 9-33 weeks). This response, which was independent of the infant's lung mechanics, appeared much later in infants with the severe form of CLD. As undeveloped peripheral chemoreceptor function has been suggested to be a key factor in sudden infant death syndrome (SIDS), the delayed development of their chemosensitivity leaves some infants with CLD unprotected against hypoxia at the age at which the risk for SIDS is highest.